Peningkatan Kemampuan Membaca Pemahaman dengan Model Pembelajaran Cooperative Integrated Reading and Composition (CIRC) Berbantuan Media Alphabet Card - Aditya Nur Rahmawati; Fadhil Purnama Adi (Didaktika Dwija Indria, 2025)
This study aims to describe the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by alphabet cards to improve reading comprehension skills in second grade students of SD Negeri 1 Babadan, Boyolali Regency. This research uses a qualitative approach by using Classroom Action Research (PTK). Data were collected through interviews with teachers and students, observation of teacher and student activities, written and oral tests, and documentation. Data validity was tested using triangulation of sources and time. The results of the study showed an improvement in students' reading comprehension skills. In the pre-action phase, the written test completion rate increased from 20% to 35% in cycle I and reached 80% in cycle II. For the oral test, the completion rate increased from 5% in cycle I to 80% in cycle II. Observations also showed an increase in effectiveness, with the average percentage of teacher observations increasing from 80.47% (cycle I) to 87.55% (cycle II), and student observations increasing from 79.11% (cycle I) to 86.42% (cycle II). The CIRC learning model assisted by alphabet cards that has been applied can improve the reading comprehension skills of second grade students of SD Negeri 1 Babadan, Sambi, Boyolali in the 2024/2025 academic year.